Perspectives and advancements in the design of nanomaterials for targeted cancer theranostics. (25th September 2020) - Tan, Yoke Ying; Yap, Pui Khee; Xin Lim, Griselda Loo; Mehta, Meenu; Chan, Yinghan; Ng, Sin Wi; Kapoor, Deepak N.; Negi, Poonam; Anand, Krishnan; Singh, Sachin Kumar; Jha, Niraj Kumar; Lim, Lay Cheng; et al.
Abstract: Cancer continues to be one of the most challenging diseases to be treated and is one of the leading causes of deaths around the globe. Cancers account for 13% of all deaths each year, with cancer-related mortality expected to rise to 13.1 million by the year 2030. Although, we now have a large library of chemotherapeutic agents, the problem of non-selectivity remains the biggest drawback, as these substances are toxic not only to cancerous cells, but also to other healthy cells in the body. The limitations with chemotherapy and radiation have led to the discovery and development of novel strategies for safe and effective treatment strategies to manage the menace of cancer. Researchers have long justified and have shed light on the emergence of nanotechnology as a potential area for cancer therapy and diagnostics, whereby, nanomaterials are used primarily as nanocarriers or as delivery agents for anticancer drugs due to their tumor targeting properties. Furthermore, nanocarriers loaded with chemotherapeutic agents also overcome biological barriers such as renal and hepatic clearances, thus improving therapeutic efficacy with lowered morbidity. Theranostics, which is the combination of rationally designed nanomaterials with cancer-targeting moieties, along with protective polymers and imaging agents has become one of the core keywords in cancer research. In this review, we have highlighted the potential of various nanomaterials for their application in cancer therapy and imaging, including their current state and clinical prospects. Theranostics has successfully paved a path to a new era of drug design and development, in which nanomaterials and imaging contribute to a large variety of cancer therapies and provide a promising future in the effective management of various cancers. However, in order to meet the therapeutic needs, theranostic nanomaterials must be designed in such a way, that take into account the pharmacokinetic and pharmacodynamics properties of the drug for the development of effective carcinogenic therapy. Highlights: Cancer is one of the leading cause of death around the globe. Theranostics is a customised approach to cancer diagnosis. These nanomaterials can address cancer treatment issues and diagnostic challenges.